Studies on Soil Physico-chemical and Ecological Changes under Twelve Years Old Five Desert Tree Species of Western Rajasthan - Aggarwal, R. K.; Gupta, J. P.; Saxena, S. K.; Muthana, K. D. (Indian Forester, 1976)
Soil physico-chemical and ecological studies in twelve years old five desert tree plantations were undertaken at Jodhpur. The results showed that density, number and height of ground flora species and above ground phytomass production was higher under Prosopis cineraria and Tecomella undulata and lowest under P. juliflora. The growth of former two species has also increased the soil fertility status with respect to organic carbon, total N and P205 and available macro and micro-nutrients. Data of moisture distribution showed higher moisture content in surface soil under P. cineraria and in 75-90 cm depth under Tecomella undulata.